Annual banned‐substance review: analytical approaches in human sports drug testing. Issue 1 (15th January 2016) - Thevis, Mario; Kuuranne, Tiia; Walpurgis, Katja; Geyer, Hans; Schänzer, Wilhelm
Abstract : The aim of improving anti‐doping efforts is predicated on several different pillars, including, amongst others, optimized analytical methods. These commonly result from exploiting most recent developments in analytical instrumentation as well as research data on elite athletes' physiology in general, and pharmacology, metabolism, elimination, and downstream effects of prohibited substances and methods of doping, in particular. The need for frequent and adequate adaptations of sports drug testing procedures has been incessant, largely due to the uninterrupted emergence of new chemical entities but also due to the apparent use of established or even obsolete drugs for reasons other than therapeutic means, such as assumed beneficial effects on endurance, strength, and regeneration capacities. Continuing the series of annual banned‐substance reviews, literature concerning human sports drug testing published between October 2014 and September 2015 is summarized and reviewed in reference to the content of the 2015 Prohibited List as issued by the World Anti‐Doping Agency (WADA), with particular emphasis on analytical approaches and their contribution to enhanced doping controls. Abstract : Detection assays for drugs and methods of sports doping published between 2014 and 2015 are critically reviewed and evaluated in context with the Prohibited List 2015 as established by the World Anti‐Doping Agency.